2006
DOI: 10.1007/s00253-006-0365-y
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, functional expression and promoter analysis of xylanase III gene from Trichoderma reesei

Abstract: In this study, the xyn3 gene from the filamentous mesophilic fungus Trichoderma reesei (Hypocrea jecorina) PC-3-7 was cloned and sequenced. Analysis of the deduced amino acid sequence of XYN III revealed considerable homology with xylanases belonging to glycoside hydrolase family 10. These results show that XYN III is distinguishable from XYN I and XYN II, two other T. reesei xylanases that belong to the glycosidase family 11. When xyn3 was expressed in Escherichia coli, significant activity was observed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 28 publications
0
29
1
2
Order By: Relevance
“…To place the bgl1 coding region in the context of the xyn3 up-and downstream regions, a blunted 2.4-kb KpnI-SpeI fragment from pCRbgl1 was inserted into the blunted SpeI site of plasmid pBxyn3ag-D0, 7) fusing it to a xyn3 downstream region, which was interrupted by a 3.1-kb DNA fragment of amdS. The resulting plasmid was opened at the SphI site in the 5 0 of the bgl1 coding region, blunted, and …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To place the bgl1 coding region in the context of the xyn3 up-and downstream regions, a blunted 2.4-kb KpnI-SpeI fragment from pCRbgl1 was inserted into the blunted SpeI site of plasmid pBxyn3ag-D0, 7) fusing it to a xyn3 downstream region, which was interrupted by a 3.1-kb DNA fragment of amdS. The resulting plasmid was opened at the SphI site in the 5 0 of the bgl1 coding region, blunted, and …”
Section: Methodsmentioning
confidence: 99%
“…Functional analyses of the promoter regions of several genes encoding cellulases and xylanases in T. reesei have been reported, [2][3][4][5][6] and we also have tried the analysis of promoters in our previous studies, [7][8][9] but information on how to select a suitable promoter to improve the saccharification of a particular biomass is lacking. Since cellobiohydrolase CBHI (Cel7A) constitutes up to 60% of secreted proteins, 10) the cbh1 promoter is considered the strongest promoter in T. reesei, hence used widely to increase the production of homo-or heterologous protein for specific purposes.…”
mentioning
confidence: 99%
“…The PC-3-7 strain, which exhibits increased cellulase activity under inducing conditions, has been used as a model of cellulase induction in our laboratory. [20][21][22] This mutant was developed following several rounds of random mutagenesis. 23,24) During screening for hyper-cellulolytic strains, we found that this strain exhibited an absence of carbon catabolite repression, and that it produced high amounts of cellulases during induction by cellulose, sophorose, and the monosaccharide L-sorbose.…”
Section: Identification Of Major Facilitator Transporters Involved Inmentioning
confidence: 99%
“…With regard to its xylanases, four have been purified and characterized: two members of glycosyl hydrolase family 11 (GH11) (XYN1 and XYN2) (3,4), the GH10 member XYN3 (5,6), and the GH30 member XYN4 (7). While the first three are all endo-␤-1,4-xylanases, XYN4 is classified as a xylan 1,4-␤-xylosidase, because it produces D-xylose as the main end product from xylan.…”
mentioning
confidence: 99%